What causes primary biliary cholangitis? - Gershwin, M. Eric (Henry Stewart Talks, 2018)
Primary biliary cholangitis epidemiology, The prevalence of PBC may be on the rise, PBC is autoimmune disease, Tolerance and xenobiotics, Immune damage, Autoreactivity and immune regulation, Bile ducts as targets, Employing new treatment strategies, PDC-E2 reactive antibodies, Pathogenesis of PBC, Benefits of early diagnosis